ASSOCIATION NOTES. - Austin, E. Burl (The Accounting Review, 1950)
The article presents various developments related to professional accounting and accountants in the U.S. Edward J. Kelley has been appointed to succeed the late Myron M. Strain as Dean of the School of Accountancy. Dean Kelley practiced as a Certified Public Accountant in San Jose prior to 1936, during which time and until 1941, he was Dean of the College of Business Administration of Santa Clara University. He has been serving until this appointment as Controller of Hastings Clothing Company in San Francisco. Howard W. Wright has been granted a leave of absence for the academic year 1950-51. Wright has been appointed Assistant to the Controller of Economic Cooperation Administration. The University of Tulsa, together with seven other sponsoring agencies, was host in April to the fourth annual Conference of Accountants. The two-day program was devoted to the general topic "Humanizing Accounts and Accountants." Noted speakers participated from all parts of the United States and representing many specialties related to accounting.